Crop wild relatives and climate change - Redden, R.; Yadav, S.S.; Maxted, Nigel; Dulloo, Mohammad Ehsan; Guarino, Luigi; Smith, Pete (Wiley, 2015)
Crop Wild Relatives and Climate Change – gives an overview of the impacts of climate change on growing environments and the challenges that agricultural production faces in coming years and decades. It explores the potential for crop wild relatives to contribute novel genetic resources to the breeding of more resilient and productive crops, and breeding technologies and biotechnological advances that are being used to incorporate key genetic traits of wild relatives into crop varieties. It also includes discussions on the importance of conserving genetic resources to ensure continued successful crop production.